Dermatopathologic emergencies part ii: Dermatopathologic and situational - Douglas H Atmatzidis; Amy R Weiss; Karl Hoegler; W Clark Lambert (Wolters Kluwer Medknow Publications, 2018)
In dermatopathology, there are several conditions which must be addressed emergently. While some conditions necessitate emergent intervention because of the pathology of the cutaneous manifestations, others require recognition of the underlying serious systemic conditions represented by the cutaneous signs and symptoms. In this part, we address rickettsial infections and eczema herpeticum as diseases which should be addressed immediately on presentation because of the seriousness and rapidity of progression of their pathology. Moreover, porphyria cutanea tarda, Birt-Hogg-Dubé syndrome, Muir-Torre syndrome, and acquired ochronosis may exemplify conditions where the cutaneous signs serve as warnings for severe systemic disease that may not be emergencies in isolation but can indicate rapid occult development of destructive and sometimes deadly noncutaneous pathology. The literature review was conducted using searches in PubMed and references to textbooks on the subjects.